BILAG-2004 index captures systemic lupus erythematosus disease activity better than SLEDAI-2000. Issue 6 (22nd May 2007) - Yee, C-S; Isenberg, D A; Prabu, A; Sokoll, K; Teh, L-S; Rahman, A; Bruce, I N; Griffiths, B; Akil, M; McHugh, N; D'Cruz, D; Khamashta, M A; et al.
Abstract : Objective: To assess the reliability of Systemic Lupus Erythematosus Disease Activity Index (SLEDAI)-2000 index in routine practice and its ability to capture disease activity as compared with the British Isles Lupus Assessment Group (BILAG)-2004 index. Methods: Patients with systemic lupus erythematosus from 11 centres were assessed separately by two raters in routine practice. Disease activity was assessed using the BILAG-2004 and SLEDAI-2000 indices. The level of agreement for items was used to assess the reliability of SLEDAI-2000. The ability to detect disease activity was assessed by determining the number of patients with a high activity on BILAG-2004 (overall score A or B) but low SLEDAI-2000 score (<6) and number of patients with low activity on BILAG-2004 (overall score C, D or E) but high SLEDAI-2000 score (⩾6). Treatment of these patients was analysed, and the increase in treatment was used as the gold standard for active disease. Results: 93 patients (90.3% women, 69.9% Caucasian) were studied: mean age was 43.8 years, mean disease duration 10 years. There were 43 patients (46.2%) with a difference in SLEDAI-2000 score between the two raters and this difference was ⩾4 in 19 patients (20.4%). Agreement for each of the items in SLEDAI-2000 was between 81.7 and 100%. 35 patients (37.6%) had high activity on BILAG-2004 but a low SLEDAI-2000 score, of which 48.6% had treatment increased. There were only five patients (5.4%) with low activity on BILAG-2004 but a high SLEDAI-2000 score. Conclusions: SLEDAI-2000 is a reliable index to assess systemic lupus erythematosus disease activity but it is less able than the BILAG-2004 index to detect active disease requiring increased treatment.